Pengaruh Spektrum Cahaya dan Lama Perendaman Benih Terhadap Pertumbuhan dan Hasil Microgreen Bunga Matahari (Helianthus annuus L.) - Feni Maulida Fajrin; Rizka Novi Sesanti; Erie Maulana; Sismanto Sismanto; Rahmadyah Hamiranti (Journal of Horticulture Production Technology, 2023)
Sunflowers are plants from the Asteraceae family which are popular as ornamental plants, as well as consumed in the form of microgreens. The problem with microgreen cultivation is that it requires light as a substitute for sunlight and is difficult to imbibition because it has a hard skin. The aims of this study were (1) to obtain the best light spectrum color on the growth and yield of sunflower microgreens, (2) to obtain the best soaking time for sunflower microgreen growth and yields, (3) to obtain the best interaction of light spectrum treatments and soaking time seed. The research method was arranged using a split plot experimental design in a randomized block design with 3 repetitions. The main plot are the light spectrum and the sub plots are the soaking time of the seeds. Variables observed: germination time, germination percentage, germination rate, microgreen height, sample weight per plot. The results showed that the white light spectrum produced the best germination percentage and germination rate, while the blue light spectrum produced the best microgreen height. Seed soaking time of 12 hours produced the best percentage of germination, germination rate, and weight per plot, while soaking time of 24 hours produced the best germination time and microgreen height. Blue light spectrum and 24 hours soaking time produced the best interaction on microgreen height, and weight per plot. White light spectrum and 12-hour soaking produced the best interaction on germination percentage.